(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The subject of improving the performance of services provided by government institutions of the important topics at the present time because of their direct contact at the service of citizens and the increased importance of these units as a result of the diversity of activities performed by the so governments of the countries and their people made sure to pay attention to the good use of those allocated to those sectors of resources and spending in the service prescribed and manage the highest level of efficiency and effectiveness and monitor the proper management of the money used in those sectors and evaluate their performance through the Supreme Audit Institutions so that they can play their role oversight and contribute to the development and improve the performance of the entities subject to the supervision and evaluation of the efficiency and effectiveness of public services goals, but we find services provided by government institutions in Iraq in general and municipal institutions in Muthanna on a particular far from the aspirations of the citizens and to the low performance levels thus research focused on the role of the external audit to assess the efficiency and effectiveness of services provided, and that of the most important findings of the research declining revenue generated by circuit municipal and rely heavily on grants they receive from the Treasury and the province to cover its expenses as well as the municipalities of Muthanna, the cost of the system within which to determine the standard cost and compare it with the actual cost of services not available, so you must municipalities rely on self-financing.